DETERMINAN CONTINUOUS PURCHASE INTENTION: VALUE DAN PERANTRUST PADA LIVE STREAMING TOKOPEDIA DI JAKARTA - NADINE SAFIRA ANNETTE SIWY; NUNO SUTRISNO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to determine the effect of Utilitarian, Hedonic, and Social Value on Continuous Purchase Intention through Trust in Streamer and Trust in Product as mediating variables in Tokopedia Live Streaming in Jakarta. Data analysis in this study was conducted quantitatively and used a descriptive and causal research design. Variables were measured using a 5-point Likert scale. This study used primary data collected through questionnaires. The sampling method used was non-probability sampling with purposive sampling techniques using 267 respondents. The research data was processed using SmartPLS 4.0 software. The data analysis technique used in this study was structural equation modeling. The results of this study indicate that Utilitarian Value, Hedonic Value, and Social Value have an influence on Trust in Streamer and Trust in Product, and Trust in Streamer and Trust in Product have an influence on Continuous Purchase Intention. This study is expected to provide input and suggestions to E-Commerce companies, especially Tokopedia, regarding the Live Streaming feature that is the object of this study, so that they can increase their market share in the Live Streaming feature in Indonesia.